Leis penais em branco e princípio da legalidade - Boaro, Guilherme (2017)
This dissertation is inserted in the research line “Contemporary Criminal-Legal Systems” and has as objective the analysis of the blank criminal laws. Intends to establish, in this regard, a scenario that allows to trace, in the light of the principle of legality, its fundamentals and bordering lines to allow the construction of criteria to its recurrence. To realize this objective, the research divides in three distinct and complementary moments. In a first analysis, proceeds to a delimitation of the idea of legality, from its paradigms, vinculated of the iluminism period, until its principological projection in the criminal law. Then, in a second moment, directs the study to the dogmatic exam of the category of the blank criminal laws (concept, fundaments, features and modalities). Finally, in a third stage of the research, it is sought to confront it with the liberal content of the principle of legality, as understood in its conformation to contemporary criminal law, in order to analyze the possibility of the category of blank criminal laws having, in its foundations and limits, its recurrence feasible.